Stevens' Handbook of Experimental Psychology 2002
DOI: 10.1002/0471214426.pas0103
|View full text |Cite
|
Sign up to set email alerts
|

Depth Perception

Abstract: This chapter contains a review of information that we use to perceive the three‐dimensional structure of the visual world. To a limited extent for near viewing we can use nonvisual signals from the accommodative state of the lens or the state of convergence of the eyes. Visual information available to one eye included image blur arising from out‐of‐focus images; overlap between images of objects at different distances serves as a cue to relative depth. Shading and shadows provide a rich source of information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 177 publications
2
14
0
Order By: Relevance
“…In other words, the retinas acts as if they were flat! As far as we could tell, this seems to be a new result [11]. Given a typical abathical distance of 1m and an interoccular distance of 6.5cm, the normal of the plane would deviate 1.86 degrees outwards from the visual axis.…”
Section: Human Visionmentioning
confidence: 70%
See 1 more Smart Citation
“…In other words, the retinas acts as if they were flat! As far as we could tell, this seems to be a new result [11]. Given a typical abathical distance of 1m and an interoccular distance of 6.5cm, the normal of the plane would deviate 1.86 degrees outwards from the visual axis.…”
Section: Human Visionmentioning
confidence: 70%
“…Under the assumption that the retina is spherical and that corresponding points are spread symmetrically around the fovea, the horopter becomes a circle known as the Vieth-Müller circle [17]. It has, however, been observed that the empirical horopter deviates from the theoretical horopter by what is known as the Hering-Hillebrand deviations [11]. The empirical horopter is always flatter than the Vieth-Müller circle.…”
Section: Human Visionmentioning
confidence: 99%
“…These include pictorial depth cues that are present in a single static image of a scene, such as occlusion, relative size, perspective, shading, texture gradients and blur [1,2]. Although such pictorial cues are valuable in interpreting three-dimensional scene structure, they generally do not provide precise quantitative information about depth.…”
Section: Introductionmentioning
confidence: 99%
“…The displays in that study contained a monocular depth cue-occlusion (see Howard, 2002). One rectangle occluded a second rectangle, which occluded the background.…”
mentioning
confidence: 99%